Intracellular levels of reactive oxygen species correlate with ABT‐263 sensitivity in non‐small‐cell lung cancer cells. Issue 10 (5th August 2020) - Ohgino, Keiko; Terai, Hideki; Yasuda, Hiroyuki; Nukaga, Shigenari; Hamamoto, Junko; Tani, Tetsuo; Kuroda, Aoi; Arai, Daisuke; Ishioka, Kota; Masuzawa, Keita; Ikemura, Shinnosuke; Kawada, Ichiro; et al.
Abstract: ABT‐263 (Navitoclax) is a BH3‐mimetic drugs targeting anti‐apoptotic B‐cell lymphoma‐2 (BCL‐2) family proteins, including BCL‐2, BCL‐xL, and BCL‐w, thereby inducing apoptosis. In small‐cell lung cancer (SCLC) cells, the response to ABT‐263 is associated with the expression of myeloid cell leukemia‐1 (MCL‐1) protein, however the efficacy of ABT‐263 in non‐small‐cell lung cancer (NSCLC) has not been thoroughly evaluated. There are currently no established biomarkers for predicting the efficacy of ABT‐263 treatment in NSCLC. We screened a panel of different NSCLC cell lines and found that ABT‐263 inhibited cell proliferation and induced apoptosis in Calu‐1, Calu‐3, and BID007 cells. Inconsistent with previous reports on SCLC, low levels of MCL‐1 did not predict the response to ABT‐263 in NSCLC cells, however we found that intracellular levels of reactive oxygen species (ROS) in cancer cells were associated with sensitivity to ABT‐263 in NSCLC cells. We also showed that increasing the level of intracellular ROS could enhance the sensitivity to ABT‐263 in NSCLC cells. In summary, we propose that the intracellular levels of ROS could be used as a potential novel biomarker for predicting a response to ABT‐263 in NSCLC. Furthermore, we show some evidence supporting the further assessment of ABT‐263 as a new therapeutic strategy in patients with NSCLC combined with agents regulating ROS levels. We believe that our findings and follow‐up studies on this matter would lead to novel diagnostic and treatment strategies in patients with NSCLC. Abstract : This article clarified the potential relationship between intracellular ROS and sensitivity to BH3‐mimetic drug, ABT‐263 in non‐small‐cell lung cancer.